The Comparison of Hegu Acupressure and Lemon Aromatherapy on Nausea and Vomiting among Cervical Cancer Patients Undergoing Chemotherapy - Anis Ardiyanti; Rinda Intan Sari; Linda Pramusinta (Fakultas Ilmu-ilmu Kesehatan, 2026)
Cervical cancer is a potentially fatal disease, making chemotherapy a necessary treatment. However, chemotherapy often causes side effects such as nausea and vomiting, which can reduce patients' motivation to continue treatment and negatively impact their well-being. Consequently, complementary therapies like Hegu acupressure and lemon aromatherapy have been explored to alleviate these symptoms. This study aimed to compare the effectiveness of Hegu acupressure therapy and lemon aromatherapy in reducing nausea and vomiting among cervical cancer patients undergoing chemotherapy. A quasi-experimental, two-group pre-posttest design was employed, using random sampling to recruit 60 respondents. The Index of Nausea, Vomiting, and Retching (INVR) was used as the assessment instrument. Data analyzed using the Wilcoxon signed-rank test and the Mann-Whitney U test. Most participants were in the early elderly age group, unemployed, and stage III cervical cancer. Statistical findings demonstrated that both Hegu acupressure (p=0.005) and lemon aromatherapy (p=0.002) significantly reduced nausea and vomiting. No significant difference was found between the two interventions (p=0.421), indicating comparable therapeutic effects. Thus, therapy can be recommended as complementary non-pharmacological interventions for managing chemotherapy-induced nausea and vomiting in cervical cancer patients. Future research is required to consider additional variables to improve the robustness and generalizability of these findings.